2008
DOI: 10.1504/ijsm.2008.019234
|View full text |Cite
|
Sign up to set email alerts
|

A review of surface integrity in machining and its impact on functional performance and life of machined products

Abstract: This paper presents an overview of the past research on Surface Integrity (SI) studies in the context of machined components from a range of work materials including stainless steels, Ni and Ti alloys, hardened steels for dies and moulds, bearings and automotive applications. Typical surface alterations such as phase transformations, microhardness and residual stress are discussed and correlated with the functional performance of the machined products. A summary of past and current modelling efforts is then pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
116
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(119 citation statements)
references
References 112 publications
(154 reference statements)
3
116
0
Order By: Relevance
“…It was reported that austenitic stainless steels belong to difficult to machine materials category because of their low thermal conductivity and high mechanical and micro structural sensitivity to strain and stress rate (M'Saoubi et al, 2008). Many of research works contributed their efforts to overcome poor machinability of austenitic stainless steels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was reported that austenitic stainless steels belong to difficult to machine materials category because of their low thermal conductivity and high mechanical and micro structural sensitivity to strain and stress rate (M'Saoubi et al, 2008). Many of research works contributed their efforts to overcome poor machinability of austenitic stainless steels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…has been made. [3] In the previous years, many studies have been carried out to explore different facets of the hard turning of alloy steel. Ramesh et al [4]examined the differences in structure and properties of white layers formed during machining of hardened AISI 52100 steel (62 HRC) at different cutting speeds.…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-precision manufacturing (UPM) technology is one of the most important methods to produce high-quality titanium alloy components with surface precision and roughness in nanometer range [2] F o r P e e r R e v i e w microstructure changes induced by machining were focus on the machined chips, there are few publications regarding the finished surface, which is more important than chips in most cases. To reveal the influence of continuous impact caused by cutting force to machined surface, a cutting experiment was conducted to discover the phase decomposition of alloy workpiece surface by using back-scattered electron microscopy [8][9] .…”
Section: Introductionmentioning
confidence: 99%